Independent Predictive Factors for Occurrence of Ischemic Priapism after Papaverine Injection - Güler, Yavuz; Erbin, Akif (Urology Journal, 2020)
Purpose: To analyze the predictive factors causing ischemic priapism following penile doppler ultrasonography (PDU) with intracavernosal papaverine injection Materials and methods: Medical records of 467 patients who underwent PDU examination following intracavernosal papaverine injection for erectile dysfunction (ED) between 2009 and 2017 were retrospectively reviewed. Patients with hematological disease anamnesis, patients taking phosphodiesterase-5 inhibitor, patients with intracavernosal injection therapy anamnesis and patients who underwent PDU with other intracavernosal vasodilator drugs other than papaverine were excluded from the study. The remaining 268 patients were divided into two groups as priapism (38 patients) and non-priapism (230 patients). The groups were compared in terms of demographic data, American Society of Anesthesiologists (ASA) score, comorbidities, international index of erectile dysfunction (IIEF) score and PDU results. The significant parameters were analyzed with binary logistic regression analysis. The receiver operating analysis was used to obtain cut-off, sensitivity and specificity values for the independent predictive factors. Results: The age, ASA score, diabetes mellitus, IIEF score, duration of ED, peak arterial and peak end diastolic venous flow values in the 20th minute were significantly different in the two groups (p<0.001). Binary logistic regression analysis found age, duration of erectile dysfunction, IIEF score, peak arterial flow and venous flow rate in the 20th minute were predictive variables for the occurrence of priapism. Conclusions: Young patients, patients with good IIEF score, patients with ED for a short time, and patients with normal peak arterial and venous flows are more prone to developing post-papaverine ischemic priapism.